Determinants of social spending in Latin America during and after the Washington consensus: A dynamic panel error-correction model analysis - Fernando Martín-Mayoral; Juan Fernández Sastre (Latin American Economic Review, 2017)
This paper examines the determinants of social spending in Latin America during the period 1990-2012 and how they differed between the years of the Washington Consensus (1990-2000) and the period that followed (2001-2012). Special attention is also paid to the evaluation of convergence towards a common upper-bounded steady state (absolute beta convergence) or to specific steady states conditioned by their country's specific determinants (conditional beta convergence). We estimate a panel error-correction version of an autoregressive distributed lag model to identify the long-term relationships between social expenditure and its determinants. Generalised methods of moments estimators are used to control the endogeneity of the regressors. Results indicate that Latin American social spending follows a conditional beta convergence process over the Washington consensus period that was mainly driven by structural differences in fiscal burdens and external debt, while during the second period it was explained by conjunctural differences in the fiscal burden, GDP per capita and the growth of trade and capital openness.
Keywords: E6; H5; I3; 330; Social spending; Latin America; Beta convergence; Washington consensus; Dynamic panel error-correction model; GMM estimators